2016
DOI: 10.1371/journal.pone.0168200
|View full text |Cite
|
Sign up to set email alerts
|

β1/2 or M2/3 Receptors Are Required for Different Gastrointestinal Motility Responses Induced by Acupuncture at Heterotopic or Homotopic Acupoints

Abstract: Acupuncture at homotopic acupoints or heterotopic acupoints is known to either inhibit or facilitate gastrointestinal motility, depending on the acupoint location. However, little effort has been made to investigate the roles of specific receptors (such as adrenergic and muscarinic acetylcholine receptors) in mediating the effects of acupuncture at heterotopic and homotopic acupoints. Different adrenergic receptor subtypes or cholinergic receptor subtypes are predominantly expressed in various sections of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…By summarizing data from existing researches, Yu [ 45 ] put forward that stimulating acupoints located at arms and legs, such as ST36 and LI11, activates vagal efferent fiber and results in positive gut motility, and stimulating acupoints distributed in the abdomen (like ST25) regulates gut motility negatively in a sympathetic dependent way. Vagotomy or knockout genes encoding M2 and M3 receptors can reduce the former action and antagonist of sympathetic nerve or deletion of genes encoding β 1 and β 2 receptors can attenuate the latter effect [ 42 44 , 46 ]. These results indicated that we can choose different acupoints for EA depending on different kinds of gastrointestinal dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…By summarizing data from existing researches, Yu [ 45 ] put forward that stimulating acupoints located at arms and legs, such as ST36 and LI11, activates vagal efferent fiber and results in positive gut motility, and stimulating acupoints distributed in the abdomen (like ST25) regulates gut motility negatively in a sympathetic dependent way. Vagotomy or knockout genes encoding M2 and M3 receptors can reduce the former action and antagonist of sympathetic nerve or deletion of genes encoding β 1 and β 2 receptors can attenuate the latter effect [ 42 44 , 46 ]. These results indicated that we can choose different acupoints for EA depending on different kinds of gastrointestinal dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The β1 and β2 receptors are expressed in the GI tract and serve as the predominant subtypes in the inhibitory effects of the SNS on GI motility[ 47 , 48 ], while the M2 and M3 receptors serve as the predominant subtypes in the excitatory effects of the PNS on GI motility[ 49 , 50 ]. The effect of acupuncture on GI motility could also be reduced by the corresponding antagonist[ 51 - 54 ] and deletion of the gene encoding the β 1&2 receptor or M 2&3 receptor[ 55 - 57 ]. In addition to the excitement effect, lower extremity acupoints also suggest an inhibitory effect on GI movement, and the inhibitory rate of ST37/LI11 on gastric movement fluctuates between 6.67%–1.33%[ 58 , 59 ].…”
Section: Autonomic Nervous System Mechanism Of Acupuncturementioning
confidence: 99%
“…The effects of acetylcholine on gastrointestinal contractility are mainly regulated by muscarinic acetylcholine receptors [ 62 ]. So the activity of muscarinic acetylcholine receptors is directly tied to the gastrointestinal motility [ 63 ]. Atropine, a muscarinic acetylcholine receptor antagonist, could be used to induce delay in gastrointestinal transit [ 10 ].…”
Section: Drug Administration Animal Modelsmentioning
confidence: 99%